Analisis Upaya Pemerintah Terhadap Produktivitas Usaha Mikro Kecil Dan Menengah Di Kabupaten Mandailing Natal - Siti Kholijah Pulungan (Al-Sharf: Jurnal Ekonomi Islam, 2022)
Micro, Small and Medium Enterprises in Indonesia are one of the contributors to national ecobomic growth, so that the existence of this business needs attention in its development so that it can make a moremeaningful contribution to rural economic growth, as well as in the absorption of  labor in the context of overcoming unemployment and reducing poverty. Micro, small and medium enterprises can absorb a lot of labor so that the unemployment rate in Indonesia can be minimized, through micro, small and medium enterprises, community workers can be empowered by micro, small and medium enterprises. This study aims to deternine the effect of the government’s offorts on the productivity of micro, small and medium enterprises in Mandailing Natal district which includes the government’s efforts on the productivity of micro, small and medium enterprises, the definition of micro, small and medium enterprises, criteria and at national and ragional levels.